Braconidae (Hymenoptera) in the collection of the Institute of Zoology, NAS of Azerbaijan Republic Part V. Subfamilies Chardichilinae, Microgasterinae and Miracinae - Abdinbekova, Arifa; Huseynova, Ellada; Kerimova, Ilhama (Contributions to Entomology = Beiträge zur Entomologie, 2017)
We present some faunistic records of braconids of the subfamilies Chardichilinae (genus Cardiochiles), Microgasterinae (genera Microplitis, Microgaster, Choeras, Cotesia, Protapanteles, Apanteles), and Miracinae (Mirax) deposited in the collection of the Institute of Zoology of the National Academy of Sciences of Azerbaijan, Baku. Localities in Azerbaijan, general distribution, and remarks on hosts are given for each taxon. Specimens of 28 species originally represented in the collection are now held by ZIN (Zoological Institute of the RAS) and are not covered further in this paper. They are the following: Apanteles albipennis (Nees, 1834), Apanteles lateralis (Haliday, 1834), Apanteles sublateralis Tobias, 1976, Apanteles rufulus Tobias, 1964, Apanteles subfirmus Abdinbekova 1969, Apanteles znoikoi Tobias 1976, Apanteles albinervis Tobias, 1964, Apanteles girkanus Tobias 1976, Apanteles negativus Tobias 1976, Apanteles subemarginatus Abdinbekova, 1969, Apanteles varifemur Abdinbekova, 1969, Apanteles brunnistigma Abdinbekova, 1969, Apanteles masallensis Abdinbekova, 1969, Apanteles kubensis Abdinbekova, 1969, Apanteles samedovi Abdinbekova, 1969, Apanteles carpatus (Say, 1836), Apanteles anarsiae Faure & Alabouvette, 1924, Cotesia subordinaria (Tobias, 1976), Cotesia rubripes (Haliday, 1834), Cotesia rufiventris (Bingham, 1906), Cotesia shemachaensis (Tobias, 1976), Protapanteles pallipes (Reinhard 1880), Protapanteles compressiventris (Muesebeck 1921), Microplitis ochraceus Szépligeti, 1896, Microplitis erythrogaster Abdinbekova, 1969, Deuterixys rimulosa (Niezabitowski, 1910), Glyptapanteles inclusus (Ratzeburg, 1844), Iconella subcamilla (Tobias, 1976).